2018
DOI: 10.1080/09593330.2017.1423396
|View full text |Cite
|
Sign up to set email alerts
|

Use of TiO2 photocatalyst supported on residues of polystyrene packaging and its applicability on the removal of food dyes

Abstract: This work proposes the use of plastic residues, more specifically polystyrene packaging, to support TiO, used as a photocatalyst in the degradation of erythrosine and Brilliant Blue food dyes. The scanning electron microscopy and Fourier transform infrared spectroscopy analyses exhibited the surface coating and the presence of TiO in the material, respectively. The UV/HO/TiO process was used in the preliminary study, given the high percentage of degradation, operational advantages and greater reductions in pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This behavior was expected, since without radiation source, it is not possible to generate the free radicals (OH•) responsible for the organic dyes degradation. The same behavior was observed by Santos et al (2018) and Nascimento Júnior et al (2018) in their photocatalytic studies with dyes. In Figure 3, the degradation behavior of the RGY dye is represented for different AOP as a function of the experiment time.…”
Section: Preliminary Testssupporting
confidence: 86%
See 2 more Smart Citations
“…This behavior was expected, since without radiation source, it is not possible to generate the free radicals (OH•) responsible for the organic dyes degradation. The same behavior was observed by Santos et al (2018) and Nascimento Júnior et al (2018) in their photocatalytic studies with dyes. In Figure 3, the degradation behavior of the RGY dye is represented for different AOP as a function of the experiment time.…”
Section: Preliminary Testssupporting
confidence: 86%
“…Oancea and Meltzer (2013) perceived that the influence of the H 2 O 2 amount applied for synthetic dyes removal obtained best degradation percentages for higher oxidant dosages. Also Pajootan et al 2017, Santos et al (2018) and Gupta et al (2011) observed in their works that the TiO 2 increase caused higher efficiency on synthetic dyes removal in aqueous solution.…”
Section: Factorial Experimental Design (2³)mentioning
confidence: 93%
See 1 more Smart Citation
“…These were exposed to solutions with the pharmaceuticals contaminants before and after being treated by the photoperoxidation and photo-Fenton processes. The toxicity assessment followed the methodology described by Santos et al [44].…”
Section: Toxicitymentioning
confidence: 99%
“…Photocatalytic materials decompose organic dyes in different mechanisms based on their chemical nature, where the reliable mechanisms are electrons and holes generated from photocatalyst or active free radicals by UV–visible light which are responsible for catalytic decomposition reactions. 14,15 The presence of transition metals enhances the charge transfer and increases the photochemical degradation process. Rauf et al revealed transition metals dopped TiO 2 photocatalytic materials for the removal of organic dyes in wastewater.…”
Section: Introductionmentioning
confidence: 99%